Analisis Jeruk dan Kulit Jeruk sebagai Larutan Elektrolit terhadap Kelistrikan Sel Volta - suci asmarani; Sri Wahyu Suciyati; Amir Supriyanto (Jurnal Teori dan Aplikasi Fisika, 2019)
It has been conducted a research to analyze Citrus sp as voltaic cell electrolyte liquid based on pH and fruit condition on its electrical properties. The research objective was to utilize citrus sp waste as an alternative source of electrical energy bio-battery. The materials required consists of a copper electrode (Cu), zinc (Zn), electrolyte liquid (50ml) from lime, lemon, medan orange and pontianak orange. Electrode copper Cu used as cathode and zinc (Zn) as anode. The conditions of liquid variations fresh, fermentation 48 hours, and putridity. The acidity level of the liquid was measured using pH meter. The best result of measuring without a load was found in putrid liquid of lemon, which was 19,36 V. Measurement using 1000? of load was obtained best result in the 48 hours fermentation of lime liquid, that are 2,369 mW, 0,762 mA and 3,11 V. For the measuring with additional LED, the best results are the liquid of lemon dan lime with permentation 48hours, with maximum 9 LED. The results are 7,144mW and 8,534 mW.